A Scoring Procedure for Malignant Narcissism Based on Personality Inventory for DSM-5 Facets. Issue 6 (24th October 2022) - Faucher, Jonathan; Savard, Claudia; Vachon, David D.; Payant, Maude; Gamache, Dominick
Abstract: The current study focuses on the development and validation of a scoring procedure for malignant narcissism using the Personality Inventory for DSM-5, a self-report measure of Criterion B from the Alternative Model for Personality Disorders. In Study 1, a prototype matching approach was used to aggregate ratings from 15 clinicians specializing in personality disorder treatment and/or assessment. Indices of inter-rater agreement and inter-rater reliability revealed high convergence as to the most important maladaptive facets for malignant narcissism. The scoring procedure, based on additive counts for score computation, included eleven Criterion B facets covering core features of malignant narcissism. Study 2 evaluated the criterion and incremental validity of the scoring procedure in a sample of 288 patients from a personality disorder treatment clinic, as well as in a sample of 1103 participants from the community. In both samples, results from nonparametric mean comparisons, receiver operating characteristic curves, bivariate Pearson correlations, and hierarchical multiple linear regressions showed significant associations between malignant narcissism and broader components of personality functioning, as well as with relevant emotional, relational, and/or behavioral features. This new scoring procedure is a simple and valid method for measuring malignant narcissism, and is suitable for clinical and research settings.